Modeling the formation of massive stars - Kuiper, Rolf (2009)
I investigate the radiation pressure problem in the formation of massive stars using a newly developed frequency dependent radiation transport module for three-dimensional hydrodynamics simulations. The nature of the radiative impact depending on the morphology of the stellar environment is examined in one-, two-, and three-dimensional monolithic collapse calculations of massive pre-stellar cores. Contrary to previous research, a highly superior frequency dependent stellar feedback is considered, the vicinity of the forming star is resolved down to 1.27 AU, and the evolution is computed for a factor of ten longer. For the first time a broad survey of the parameter space is possible. The simulations demonstrate the need of including the dust condensation front to compute the radiative feedback correctly. Earlier calculations, which ignore these physics, lead to an artificial truncation of the accretion phase. The most fundamental result is that the formation of a massive accretion disk in slowly rotating cores bypasses the radiative flux through the optically thin atmosphere, enabling steady accretion. A revealed close-by gravitational instability in the disk drives a sufficiently high accretion rate to overcome the residual stellar radiation feedback. This mechanisms allow the star to grow far beyond any limit found in earlier calculations.
Keywords: Hochschulschrift; Fragmentierung; Hydrodynamik; Strahlungstransport; Akkretionsscheibe; Akkretion; Massereicher Stern; Sternentstehungsgebiet